MR spectroscopic imaging at 3 T and outcomes in surgical epilepsy. (10th March 2021) - Pan, Jullie W.; Antony, Arun; Tal, Assaf; Yushmanov, Victor; Fong, Joanna; Richardson, Mark; Schirda, Claud; Bagic, Anto; Gonen, Oded; Hetherington, Hoby P.
Abstract : For the spectroscopic assessment of brain disorders that require large‐volume coverage, the requirements of RF performance and field homogeneity are high. For epilepsy, this is also challenging given the inter‐patient variation in location, severity and subtlety of anatomical identification and its tendency to involve the temporal region. We apply a targeted method to examine the utility of large‐volume MR spectroscopic imaging (MRSI) in surgical epilepsy patients, implementing a two‐step acquisition, comprised of a 3D acquisition to cover the fronto‐parietal regions, and a contiguous parallel two‐slice Hadamard‐encoded acquisition to cover the temporal‐occipital region, both with T R / T E = 2000/40 ms and matched acquisition times. With restricted (static, first/second‐order) B 0 shimming in their respective regions, the Cramér‐Rao lower bounds for creatine from the temporal lobe two‐slice Hadamard and frontal‐parietal 3D acquisition are 8.1 ± 2.2% and 6.3 ± 1.9% respectively. The datasets are combined to provide a total 60 mm axial coverage over the frontal, parietal and superior temporal to middle temporal‐occipital regions. We applied these acquisitions at a nominal 400 mm 3 voxel resolution in n = 27 pre‐surgical epilepsy patients and n = 20 controls. In controls, 86.6 ± 3.2% voxels with at least 50% tissue (white + gray matter, excluding CSF) survived spectral quality inclusion criteria. Since all patients were clinically followed for at least 1 year after surgery, seizure frequency outcome was available for all. The MRSI measurements of the total fractional metabolic dysfunction (characterized by the Cr/NAA metric) in FreeSurfer MRI gray matter segmented regions, in the patients compared with the controls, exhibited a significant Spearman correlation with post‐surgical outcome. This finding suggests that a larger burden of metabolic dysfunction is seen in patients with poorer post‐surgical seizure control. Abstract : Two‐slice cascaded Hadamard spectroscopic image in controls. A, Scout MRI and magnitude NAA images. B, Sample spectra (positions indicated in A) showing the Cramér‐Rao lower bound (%) for NAA, Cr and Cho. The raw with baseline, residual and fitted spectra are shown. C, For two subjects, regressions of Cr/NAA with voxel GM fraction are shown from the c‐HSI (blue) and the adjacent 3D (gray) acquisitions, finding non‐significantly different slopes and intercepts. D, A plot of the CRLB (%) versus calculated √(LW)/SNR shows similar correlations for the 3D and c‐HSI acquisitions, both significant ( p < 0.001 for both), with R = 0.67 and R = 0.64 respectively.